JURIDICAL REVIEW OF LEGAL PROVISIONS FOR THE IMPLEMENTATION AND UTILIZATION OF THE CONVERSION OF FOREST LAND INTO CAPITALISTS-ORIENTED PLANTATIONS - Elly Kristiani Purwendah; Daniel Joko Wahyono (Ganesha Law Review, 2024)
This research aims to find out how the legal provisions for the implementation and use of land conversion into plantation forests are capitalistic oriented. This research uses a normative juridical research method with a type of approach, namely a statutory and regulatory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials, obtained by conducting literature studies. The results of the research show that the conversion of forest land into plantation land is stated in Government Regulation Number 64 of 1957 concerning Forestry Deregulation, Law Number 5 of 1967 concerning Forestry and was later replaced by Law Number 41 of 1999. In its implementation the existing regulations It turns out that this has not been rooted in the legal ideology, social system and political system of the constitution, and the Basic Agrarian Principles regulations. It seems that the use of forests that is managed and oriented towards capitalists cannot be used as a measure of the government's success in economic development, considering that there are still many inequalities and problems that have occurred so far. Considering the negative impacts rather than the function of land which is increasingly expanding and wasted.